Application of knowledge-enabled customer relationship management model. (6th April 2012) - Wu, Chunte; Lin, Yichen; Liu, Chehung
Application of collaborative marketing through knowledge-enabled customer relationship management (KCRM) systems offers a great opportunity to increase customer value and provides a way to systematically attract, acquire and retain customers. A strategic KCRM framework is introduced to classify the subjects by customer-oriented perspective. This study takes a leading beauty enterprise in Asia as an example and focuses on its franchise stores to perform a case study. The KCRM model was adopted to know what, how and why customer knowledge is so important to service industry. From the responses of the surveyed beauty enterprise, it is deduced how the companies can develop their customer-connection strategies based on their current and future positions in four dimensions of the value compass model. Moreover, this study presents a conceptual model of KCRM including strategy and process to see how knowledge management systems can help customer relationship management systems implementation and increase profits through collaborative marketing.